Nanobiotechnology human health and the environment - Dhawan, Alok; Singh, Sanjay; Kumar, Ashutosh; Shanker, Rishi (Taylor & Francis, 2018)
This book combines the contributions from the experts of material science, molecular biology, toxicology bio-organic and bio-inorganic chemistry, toxicologists and environmental and food technology etc. to fathom the full scope of current and future of developments in the area of Nanobiotechnology. This book can also be used as text book for graduate students as an essential reference material, and as an reading material for general readers having a curiosity in Nanobiotechnology.--Provided by publisher.